Synthesis, Molecular Docking Study, Anti-Oxidant and Cytotoxicity Evaluation of New Spiro Six Membered Ring Derivatives of 5-nitro isatin - Hala Ayad Mohamed Rasheed; Suaad M. H. Al-Majidi (Iraqi Journal of Pharmaceutical Sciences, 2024)
Spiro-5-nitro isatino six memberd ring (quinazoline-4-one, thiazine-4-one and oxazine-4-one) respectively were produced by a cycloaddition of 5-nitro isatin Schiff bases [1–5] with anthranilic acid, o-mercapto benzoic acid and salicylic acid. 1HNMR and 13CNMR nuclear magnetic resonance spectroscopies, as well as Fourier-transform infrared spectroscopy, were used to identify the structures of the obtained compounds. These spiro-5-nitro isatin are of interest to us due to their potential antioxidant and anticancer properties. The MTT assay ((3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide)) was used to examine in vitro bioactivity testing against breast cancer (MCF-7) cell lines which compound 14 (IC50=79.85, IC50=39) after 24 hours and 48 hours showed good cytotoxicity compared with drug reference tamoxifen. synthesized compounds 6-20 were evaluated for against antioxidant activity by using DPPH assay. In molecular docking, Promising compounds were used to reveal potential cytotoxic activity mechanisms.